CLASSROOM ACTION RESEARCH AND LESSON STUDY: HOW DO THEY WORK FOR LECTURERS AND HIGH SCHOOL ENGLISH TEACHERS - Zul Amri (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
Classroom Action Research (CAR) has become the main policy of education in Indonesia. It has been a subject at some higher learning institutions, no matter public or private one. Universitas Terbuka, or Open University has also put it as a compulsory subject for its students. It has been trained to education practitioners at all levels of education in Indonesia. The outcome has been used to help practitioners to get promotion in their careers. In line with that, Lesson Study (LS) has become more popular in Indonesia right now. It helps the teacher improve the learning process without having to end with a report. CAR has four steps, Planning, Action, Observation, and Reflection while LS has only three, namely, Plan, Do, and See. When the teachers are not interested in writing research report, LS can be the choice even though it may also be ended with research report.